Ethiopia’s Emerging Counter-Hydro Hegemonic Influence: Changing the Tides of the Blue Nile Waters for an “equitable” Basin-Wide System (Cooperation and Integration) - Hailu, Dawit (Université d'Ottawa | University of Ottawa, 2013)
Recent years have seen the emergence of new hydro-political relations among eleven riparian states in the Nile River basin, challenging the highly contested and imbalanced water-sharing arrangements that resulted from the historical-colonial-legal settlement between Egypt, Sudan, and Britain. Lead by Ethiopia, all upstream riparian states are today mobilizing behind a more “equitable” paradigm to challenge Egypt’s unilateral hydro-hegemony. The aim of this research paper is to identify the key driving forces behind Ethiopia’s emerging counter-hegemonic influence against Egypt’s hydro-hegemonic management that controls access to the Blue Nile water resources. The paper first discusses how Ethiopia continues to challenge the status-quo and changes old bellicose geo-political rhetoric of fear and mistrust by employing various counter-hydro hegemonic strategies.1 Applying the theoretical, historical, legal, political, and statistical methods, the research demonstrates that Ethiopia has appeared as the main shareholder of the Nile, and has been relatively successful in achieving on-going negotiations and cooperation for domestic interest and basin-wide “benefit-sharing.” The paper concludes that this could potentially advance long-term socio-economic and political stability in the Horn of Africa, and thus help towards eradicating enduring poverty.